PRACTICAL GUIDE FOR FINAL YEAR PROJECT IN SOCIAL SCIENCE 2022 - Noor'ain, Aini; Adam Andani, Mohammed; Goy, Siew Ching; Haslina, Hashim; Mohd Shazani, Masri; Sharifah Sophia, Wan Ahmad (Faculty of Social Sciences and Humanities, 2022)
Final Year Project (FYP) is a research project for undergraduates in social science. Those of you who have yet to attempt it may have an idea of what an FYP is, most probably coming from your seniors. What you may have heard were essentially subjective responses coming from personal experiences of those who have gone through it. Just like any form of subjective experiences, it tells a particular story applicable to a particular person. In this section, we present an objective perspective that has a general application. In other words, what you will discover in Part 1 is a common convention pertaining to undergraduate research as practiced in the social sciences. You will gain a factual understanding of FYP and the path that lies ahead.